Probing the geometric constraints of RNA binding via dynamic covalent chemistry. Issue 17 (1st September 2016) - McAnany, John D.; Reichert, John P.; Miller, Benjamin L.
Graphical abstract: Abstract: Dynamic Combinatorial Chemistry (DCC) has proven to be a reliable method for identifying hit compounds for target nucleic acid (DNA and RNA) sequences. Typically, these hit compounds are subjected to a lengthy process of optimization via traditional medicinal chemistry. Here, we examine the potential of DCC to also generate and test variations on a hit compound as a method for probing the binding site of an RNA-targeted compound. Specifically, we demonstrate that addition of linker dithiols to a disulfide library containing a known binder to the HIV-1 frameshift-stimulatory RNA (a critical regulator of the HIV life cycle) can yield a mixture of new bridged structures incorporating the dithiol, depending on dithiol structure. Equilibration of this library with the HIV FSS RNA resulted in selection of the original disulfide in preference to bridged structures, suggesting incorporation of the bridge is not compatible with this particular binding site. Application of this strategy to other RNA targets should allow for rapidly profiling the affinity of modified compounds.